2018
DOI: 10.1364/ao.57.006164
|View full text |Cite
|
Sign up to set email alerts
|

Rectangular-structure-based pose estimation method for non-cooperative rendezvous

Abstract: Pose estimation for spacecraft is widely recognized as an important technology for space applications. Many space missions require accurate relative pose between the chaser and the target spacecraft. Stereovision is a usual mean to estimate the pose of non-cooperative targets during proximity operations. In this paper, an accurate algorithm for pose estimation is proposed by taking advantage of the geometric structure of the object. With stereo cameras, our approach employs the corners of the solar panel as fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…To satisfy the demands of motion control parameter input, the results achieved based on the visual feedback scheme of relative quaternion estimation [15] and coupled relative translation [16] are referenced for attitude control and orbit tracking. To enrich the available feature information, as highlighted in [17], a precise method for pose estimation by exploiting the object geometric structure is significantly effective, employing the corners of the solar panel as features. Moreover, [18], [19] suggested that the information-rich edge contour features lead to the advantages of small calculation, stable extraction, and strong anti-noise ability.…”
Section: Introductionmentioning
confidence: 99%
“…To satisfy the demands of motion control parameter input, the results achieved based on the visual feedback scheme of relative quaternion estimation [15] and coupled relative translation [16] are referenced for attitude control and orbit tracking. To enrich the available feature information, as highlighted in [17], a precise method for pose estimation by exploiting the object geometric structure is significantly effective, employing the corners of the solar panel as features. Moreover, [18], [19] suggested that the information-rich edge contour features lead to the advantages of small calculation, stable extraction, and strong anti-noise ability.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers use the 3D point cloud feature matching techniques. These techniques firstly extract geometric features such as points, lines [26] and planes [27], [28] or feature descriptors [22], [29] of the target 3D point cloud, then adopt the corresponding feature matching methods to estimate the pose of the non-cooperative target. Others use the 3D point cloud direct registration approaches [30], adopting the iterative closest point (ICP) method [35] and directly registering the XYZ coordinates between two point clouds to achieve pose estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [8] used parallel binocular cameras to estimate the pose of a non-cooperative target based on stereo matching and 3D restructuring. Zhang et al [9,10] proposed optimization-based methods to estimate the relative pose using stereo cameras, and the geometric structure of the non-cooperative target was exploited to improve the accuracy. Deng et al [11] implemented an on-board binocular vision-based system to estimate the pose of Unmanned Aerial Vehicles (UAVs) for autonomous aerial refueling.…”
Section: Introductionmentioning
confidence: 99%